Proteomic Charting of Imipenem Adaptive Responses in a Highly Carbapenem Resistant Clinical Enterobacter roggenkampii Isolate - Suruchi Nepal; Sandra Maaß; Stefano Grasso; Francis M. Cavallo; Jürgen Bartel; Dörte Becher; Erik Bathoorn; Jan Maarten van Dijl (MDPI AG, 2021)
Gram-negative bacteria belonging to the Enterobacter cloacae complex are increasingly implicated in difficult-to-treat nosocomial infections, as exemplified by a recently characterized highly carbapenem-resistant clinical Enterobacter roggenkampii isolate with sequence type (ST) 232. While mechanisms of carbapenem resistance are well-understood, little is known about the responses of highly drug-resistant bacteria to these antibiotics. Our present study was therefore aimed at charting the responses of the E. roggenkampii ST232 isolate to the carbapenem imipenem, using a 'stable isotope labeling of amino acids in cell culture' approach for quantitative mass spectrometry. This unveiled diverse responses of E. roggenkampii ST232 to imipenem, especially altered levels of proteins for cell wall biogenesis, central carbon metabolism, respiration, iron-sulfur cluster synthesis, and metal homeostasis. These observations suggest a scenario where imipenem-challenged bacteria reduce metabolic activity to save resources otherwise used for cell wall biogenesis, and to limit formation of detrimental reactive oxygen species at the cytoplasmic membrane due to respiration and Fenton chemistry. We consider these observations important, because knowing the adaptive responses of a highly resistant bacterium of the E. cloacae complex to last-resort antibiotics, such as imipenem, provides a 'sneak preview' into the future development of antibiotic resistance in this emerging group of pathogens.